Aluthge Transformation of Quasi n-class Q and quasi n- class Q* Operators (European Journal of Pure and Applied Mathematics, 2018)
In this paper, a new class of operators called quasi n-class Q and quasi n-class Q*operators are introduced and studied some properties. Quasi n-class Q and quasi n-class Q* composition and weighted composition operators on L2() and H2() are characterized. Also we discuss quasi n-class Q and quasi n-class Q composite multiplication operator on L2 space and Aluthge transformation of these class of operators are obtained.